Proclaiming a Classic : The Canonization of Orlando Furioso - Javitch, Daniel (Book collections on Project MUSE., 2014)
Despite its immediate popularity and its acclaim as a modern equal of the ancient epics, Ariosto's Orlando Furioso (published in its final version in 1532) was for learned readers a perplexing work: it mixed romance, epic, and lyric poetry, poked fun at its marvelous and outmoded chivalric matter, contained many interrupted narrative threads, and included base and lowborn characters. In exploring the literary debates involved in elevating the Furioso to the rank of a classic, Daniel Javitch maintains that this was the first work of modern poetry to provoke widespread critical controversy, a.